Intervención psicopedagógica para desarrollar la conciencia fonológica de una estudiante de primer grado de la Unidad Educativa del Milenio Bernardo Valdivieso, 2023 - Cuenca Rivera, María Guadalupe (2023)
The objective of this Curricular Integration Work was: To implement the psycho-pedagogical intervention through the LOLE program to develop phonological awareness in the first grade student at Bernardo Valdivieso Millennium Educational Unit, 2023. To fulfill this purpose, a quali-quantitative approach was used, with a case study design, descriptive and cross-sectional. The semi-structured interview, the psycho-pedagogical form and the PECO test were applied. In the interview, the teacher indicated that the student in the syllabic component identifies and segments, but does not manipulate, while in the phonemic component she has serious difficulties in identifying, adding, omitting and substituting; the results of the PECO test show a low evaluation in the level of syllabic and phonemic phonological awareness; the application of the psycho-pedagogical intervention through the LOLE program was structured in 32 didactic units divided into 2 modules, the first of rhymes and syllables and the second of phonemes; the achievements reached after the intervention register a very high evaluation in syllabic knowledge, phonetic knowledge and the total of the test, identification and omission tasks, although, in the addition task a high evaluation was evidenced, these data prove the development of phonological awareness going from a low to a very high evaluation and allow concluding that the psycho-pedagogical intervention through the LOLE program developed the phonological awareness of the student.